Default Positions: How Neuroscience’s Historical Legacy has Hampered Investigation of the Resting Mind - Callard, Felicity; Smallwood, Jonathan; Margulies, Daniel S. (Frontiers in Psychology, 2012)
The puzzle of the brain and mind at rest – their so-called default state – is strongly influenced by the historical precedents that led to its emergence as a scientific question. What eventually became the default mode network (DMN) was inaugurated via meta-analysis to explain the observation that the baseline “at rest” condition was concealing a pattern of neural activations in anterior and posterior midline brain regions that were not commonly seen in external, task-driven experiments. One reason why these activations have puzzled scientists is because psychology and cognitive neuroscience have historically been focused on paradigms built around external tasks, and so lacked the scientific and theoretical tools to interpret the cognitive functions of the DMN. This external-focused bias led to the erroneous assumption that the DMN is the primary neural system active at rest, as well as the assumption that this network serves non-goal-directed functions. Although cognitive neuroscience now embraces the need to decode the meaning of self-generated neural activity, a more deliberate and comprehensive framework will be needed before the puzzle of the wandering mind can be laid to rest.